Synthesis of fluorene-based polyelectrolytes tethering different counterions for single-component white light-emitting electrochemical cells - Yang, Sheng-Hsiung; Tsai, Chia-Sheng; Liu, Bo-Cun; Su, Hai-Ching (My University, 2013)
A series of polyfluorene (PF) electrolytes bearing Br-, BF4-, or PF6- counterions were synthesized and characterized. 2,1,3-benzoselenadiazole moieties were incorporated into polymer main chains to produce single-component white light-emitting polymers. The thermal stability of Br-containing ionic PF was decreased because of the Hofmann elimination occurred at higher temperature. By replacing Br- with BF4- or PF6- counterions, the thermal stability of polymers was significantly improved. The emission intensity around 550 nm was decreased for ionic polyelectrolytes. The optimized spin-coated light-emitting electrochemical cell (LEC) with the configuration of ITO/PEDOT/polymer/Ag showed a maximum luminescence efficiency of 1.56 lm/W at a low operation bias of 3 V. The single-component LEC device exhibited pure white light emission with CIE\'1931 coordinates approaching (0.33, 0.33) and high color rendering index (CRI > 85), referring to its potential use in solid-state-lighting application.
Keywords: polyelectrolytes; counterions; light-emitting electrochemical cells; solid-state lighting